2015
DOI: 10.1093/heapol/czv059
|View full text |Cite
|
Sign up to set email alerts
|

Behaviours and opinions towards outdoor smoking bans and cigarette littering in Baja California, Mexico

Abstract: Outdoor smoking is still frequent in outdoor areas where people gather, and an important source of littering. We found substantial public support towards the outdoor smoking ban, which should translate into easier implementation and compliance in Baja California, Mexico.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…This is similar to numbers reported in other studies. Basto-Abreu et al asked smokers in urban areas of Baja California, Mexico how many out of every ten cigarettes they toss to the ground [34]. Self-reports were that they littered 45% of cigarette butts they smoked.…”
Section: Littering Rates and Gendermentioning
confidence: 99%
“…This is similar to numbers reported in other studies. Basto-Abreu et al asked smokers in urban areas of Baja California, Mexico how many out of every ten cigarettes they toss to the ground [34]. Self-reports were that they littered 45% of cigarette butts they smoked.…”
Section: Littering Rates and Gendermentioning
confidence: 99%
“…(2014) conducted an observational study in New Zealand and found that 84% of the people who smoke at bus and train stations, litter their cigarette butts even though trash bins are available and in sight. A study in a developing country (i.e., Mexico) found that a smoking ban was not effective in reducing cigarette littering in open public places, such as parks and beaches (Basto‐Abreu et al., 2016). This suggests that cigarette butt littering is a problem faced in both developing and developed countries and that the solutions are unfortunately not as straightforward as simply imposing smoking bans.…”
Section: Discussionmentioning
confidence: 99%
“…Basto‐Abreu et al. (2016) examined the effects of a smoking ban in Mexico and found that the ban was generally ineffective in reducing cigarette butt littering. A study in Ghana suggests that an already littered environment and the lack of authorities’ interest are the main reasons for increased littering (Van Dyck et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations